Clinical presentation of ulcerative colitis among Bangladeshi population twenty years experience from a tertiary care hospital in Bangladesh - Mohammad Shoaib Chowdhury; Md. Masudur Rahman Khan; Md. Zahidur Rahman; Madhusudan Saha; Guru Prashad Dhakal; Projesh Kumar Roy; A.S.M.A. Raihan (Bangabandhu Sheikh Mujib Medical University Journal, 2016)
Background: The prevalence of Ulcerative colitis has been increasingly reported from Western countries as well as other Asian countries. Our personal experience shows that Ulcerative colitis is not uncommon in our country and is being diagnosed more commonly. So, there is need to study the disease pattern in our country. Objective: To find out the clinical presentation, among Bangladeshi population.